2021
DOI: 10.1021/acs.jproteome.1c00155
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope-Resolved Metabolomics Reveals the Abnormal Brain Glucose Catabolism in Depression Based on Chronic Unpredictable Mild Stress Rats

Abstract: The severe harm of depression to human life has attracted great attention to neurologists, but its pathogenesis is extremely complicated and has not yet been fully elaborated. Here, we provided a new strategy for revealing the specific pathways of abnormal brain glucose catabolism in depression, based on the supply of energy substrates and the evaluation of the mitochondrial structure and function. By using stable isotope-resolved metabolomics, we discovered that the tricarboxylic acid cycle (TCA cycle) is blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…Previous studies reported that mitochondrial function is strongly connected to depression [ 43 ]. Other researchers have reported that chronic stress can inhibit oxidative phosphorylation in mitochondria, disrupt the MMP, and damage the mitochondrial structures in various regions of mouse brains, such as the hippocampus and the prefrontal cortex [ 44 , 45 ]. In addition, disruption of the TCA cycle has been shown to reduce ATP production in a CMS-induced rat model of depression [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that mitochondrial function is strongly connected to depression [ 43 ]. Other researchers have reported that chronic stress can inhibit oxidative phosphorylation in mitochondria, disrupt the MMP, and damage the mitochondrial structures in various regions of mouse brains, such as the hippocampus and the prefrontal cortex [ 44 , 45 ]. In addition, disruption of the TCA cycle has been shown to reduce ATP production in a CMS-induced rat model of depression [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Some studies revealed that CUMS can result in abnormal mitochondrial morphology, such as the mitochondrial rupture and impairment in hippocampal astrocytes, and the significant mitochondrial swelling, broken mitochondrial cristae, and decreased mitochondrial matrix density in hippocampus. 17,18 Additionally, our previous study demonstrated that the prenatal dexamethasone (Dex) exposure leads to depression-like behavior and mitochondrial damage in hippocampus, including a decrease in cristae density or even the disappearance, vacuole formation by the mitochondrial outer membrane extension, as well as the intermembrane space expansion, which can be improved by exercise. 11 Taken together, these studies corroborate the close coupling between the abnormal mitochondrial morphology and the development of depression.…”
Section: Mitochondrial Morphology and Depre Ss Ionmentioning
confidence: 99%
“…Metabolomics employs liquid chromatography-mass spectrometry (LC-MS), gas chromatography (GC)-MS, and so on to analyze micromolecule of biological samples qualitatively and quantitatively for exploring the pathophysiological mechanism of life process (Ding and Mohan, 2016 ; Wishart, 2016 ). Metabolomics has been widely used to study the pathogenesis of depression (Ling-Hu et al, 2021 ; Pu et al, 2021 ). An increasing body of evidence suggests that olfactory bulb dysfunction is closely associated with depression.…”
Section: Introductionmentioning
confidence: 99%